Aftonbladet 1830's - Språkbanken Text (University of Gothenburg, 2024)
Part of the collection Kubhist2

Del av samlingen Kubhist2
Aftonbladet 1830-talet
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik